Electromagnetic Field‐Programmed Magnetic Vortex Nanodelivery System for Efficacious Cancer Therapy. Issue 18 (18th July 2021) - Liu, Xiaoli; Zhang, Yifan; Guo, Yu; Jiao, Wangbo; Gao, Xiao; Lee, Wee Siang Vincent; Wang, Yanyun; Deng, Xia; He, Yuan; Jiao, Ju; Zhang, Ce; Hu, Guoqing; et al.
Abstract: Effective delivery of anticancer drugs into the nucleus for pharmacological action is impeded by a series of intratumoral transport barriers. Despite the significant potential of magnetic nanovehicles in electromagnetic field (EF)‐activated drug delivery, modularizing a tandem magnetoresponsive activity in a one‐nanoparticle system to meet different requirements at both tissue and cellular levels remain highly challenging. Herein, a strategy is described by employing sequential EF frequencies in inducing a succession of magnetoresponses in the magnetic nanovehicles that aims to realize cascaded tissue penetration and nuclear accumulation. This nanovehicle features ferrimagnetic vortex‐domain iron oxide nanorings coated with a thermo‐responsive polyethylenimine copolymer (PI/FVIOs). It is shown that the programmed cascading of low frequency (L f )‐EF‐induced magnetophoresis and medium frequency (M f )‐EF‐stimulated magneto‐thermia can steer the Doxorubicin (DOX)‐PI/FVIOs to the deep tissue and subsequently trigger intracellular burst release of DOX for successful nuclear entry. By programming the order of different EF frequencies, it is demonstrated that first‐stage L f ‐EF and subsequent M f ‐EF operation enables DOX‐PI/FVIOs to effectively deliver 86.2% drug into the nucleus in vivo . This nanodelivery system empowers potent antitumoral activity in various models of intractable tumors, including DOX‐resistant MCF‐7 breast cancer cells, triple‐negative MDA‐MB‐231 breast cancer cells, and BxPC‐3 pancreatic cancer cells with poor permeability. Abstract : A magnetic nano‐delivery system is developed to achieve drug nuclear delivery in vivo for efficient cancer therapy. By programming the order of different electromagnetic field (EF) frequencies, the first‐stage low frequency‐EF‐induced magnetophoresis and subsequent medium frequency ‐EF‐stimulated magneto‐thermia, enables drug‐carrying magnetic vortex nanorings to realize cascaded tissue penetration and drug nuclear accumulation in vivo. This nanodelivery system empowers potent antitumoral activity.